Specific Lexical-Semantic Features of the Lexeme "Daryo" - D. M. Jamolitdinova; Mehmonova Sarvinoz Ishaq (International Journal on Integrated Education, 2022)
The Uzbek language, one of the oldest and richest languages in the world, is a symbol of our national identity and independent statehood, a priceless spiritual wealth and a great value for our people. Life is a very complicated thing. As long as you live in it, there are secrets that are known to you and us and have not yet been revealed. Knowing, realizing and understanding them remains an unsolvable puzzle for humanity. It talks about the name, creation and essence of everything. Existence, that is, the universe, does not exist without names, and it is born and dies with those names. We live by that name, understand and communicate with them. I found it necessary to think about the lexical-semantic features of the lexeme "River" in this article. And I hope that in this process we will be able to find answers to our questions.